Effect of Pelvic Bone Marrow Sparing Intensity Modulated Radiation Therapy on Acute Hematologic Toxicity in Rectal Cancer Patients Undergoing Chemo-Radiotherapy - Huang, Wei; Dang, Jun; Li, Ying; Cui, Hai-xia; Lu, Wen-li; Jiang, Qing-feng (Frontiers in Oncology, 2021)
Background: While chemo-radiotherapy improves local control in patients with locally advanced rectal cancer, it can also increase acute hematological (HT) toxicity, which leads to poor outcomes. Patients receiving bone marrow radiation have been shown to develop acute HT. However, the safety and efficacy of bone marrow sparing is undermined. The aim of our study was to explore the feasible dosimetric constraints for pelvic bone marrow (PBM) that can be widely used in rectal cancer patients undergoing chemo-radiotherapy. Methods: 112 rectal cancer patients were selected and divided into the PBM sparing IMRT group (60 cases) and the non-PBM sparing IMRT group (52 cases). All patients underwent pelvic radiotherapy with concurrent capecitabine-based chemotherapy. The PBM dosimetric constraints in the PBM sparing IMRT group were set to:V10≤85%, V20≤65% and V30≤45%. An independent sample t test was applied for the dose-volume parameters, and Chi-squared analysis was applied for clinical parameters and adverse events. Results: The radiation dose to PBM (V5~V45, Dmean, P<0.05), PBM sub-regions (V10~V35, Dmean, P<0.05) and both femoral heads (V5~V40, Dmean, P<0.05) decreased significantly in the PBM sparing IMRT group compared with that of the non-PBM sparing IMRT group (P<0.05). There was no significant difference in any dose-volume parameters of the bladder and small bowel in either groups, and none in the planning target volume (PTV) dose homogeneity and conformity (P>0.05). For acute HT observation, the incidence of grade 3 acute HT (2=7.094, P=0.008) was significantly reduced in patients treated with PBM sparing IMRT compared with patients treated with non-PBM sparing IMRT. There was no statistical difference in the incidence of vomiting, diarrhea, fatigue, anorexia, nausea, hand-foot syndrome, cystitis, perianal pain and perianal dermatitis in patients of both groups (P >0.05). Conclusions: Applying PBM dosimetric constraints (V10≤85%, V20≤65% and V30≤45%) can significantly reduce the radiation dose to PBM. The patients treated with PBM sparing IMRT had a lower incidence of acute HT compared with those treated with non-PBM sparing IMRT. Applying the PBM dosimetric constraints proposed by our study can benefits the patients with rectal cancer undergoing capecitabine-based chemo-radiotherapy.